The redox-sensitive module of cyclophilin 20-3, 2-cysteine peroxiredoxin and cysteine synthase integrates sulfur metabolism and oxylipin signaling in the high light acclimation response - Müller, Sara; Wang, Shanshan; Sticht, Carsten; Torre, Carolina de la; Wirtz, Markus; Hell, Rüdiger (The plant journal, 2017)
The integration of redox- and reactive oxygen species-dependent signaling and metabolic activities is fundamental to plant acclimation to biotic and abiotic stresses. Previous data suggest the existence of a dynamically interacting module in the chloroplast stroma consisting of cyclophilin 20-3 (Cyp20-3), O-acetylserine(thiol)lyase B (OASTL-B), 2-cysteine peroxiredoxins A/B (2-CysPrx) and serine acetyltransferase 2;1 (SERAT2;1). The functionality of this COPS module is influenced by redox stimuli and oxophytodienoic acid (OPDA), which is the precursor for jasmonic acid. The concept of an integrating function of these proteins in stress signaling was challenged by combining transcriptome and biochemical analyses in Arabidopsis mutants devoid of oastlB, serat2;1, cyp20-3 and 2-cysprxA/B, and wild-type (WT). Leaf transcriptomes were analyzed 6 h after transfer to light intensity 10-fold in excess of growth light or under growth light. The survey of KEGG-based gene ontology groups showed common upregulation of translation- and protein homeostasis-associated transcripts under control conditions in all mutants compared with WT. The results revealed that the interference of the module was accompanied with disturbance of carbohydrate, sulfur and nitrogen metabolism, and also citric acid cycle intermediates. Apart from common regulation, specific responses at the transcriptome and metabolite level linked Cyp20-3 to cell wall-bound carbohydrates and oxylipin signaling, and 2-CysPrx to photosynthesis, sugar and amino acid metabolism. Deletion of either OASTL-B or SERAT2;1 frequently induced antagonistic changes in biochemical or molecular features. Enhanced sensitivity of mutant seedlings to OPDA and leaf discs to NaHS-administration confirmed the presumed functional interference of the COPS module in redox and oxylipin signaling.